Biosafety risk assessment for production of candidate vaccine viruses to protect humans from zoonotic highly pathogenic avian influenza viruses. Issue 2 (28th October 2019) - Chen, Li‐Mei; Donis, Ruben O.; Suarez, David L.; Wentworth, David E.; Webby, Richard; Engelhardt, Othmar G.; Swayne, David E.
Abstract: A major lesson learned from the public health response to the 2009 H1N1 pandemic was the need to shorten the vaccine delivery timeline to achieve the best pandemic mitigation results. A gap analysis of previous pre‐pandemic vaccine development activities identified possible changes in the Select Agent exclusion process that would maintain safety and shorten the timeline to develop candidate vaccine viruses (CVVs) for use in pandemic vaccine manufacture. Here, we review the biosafety characteristics of CVVs developed in the past 15 years to support a shortened preparedness timeline for A(H5) and A(H7) subtype highly pathogenic avian influenza (HPAI) CVVs. Extensive biosafety experimental evidence supported recent changes in the implementation of Select Agent regulations that eliminated the mandatory chicken pathotype testing requirements and expedited distribution of CVVs to shorten pre‐pandemic and pandemic vaccine manufacturing by up to 3 weeks.